Hyperalgesia and Central Sensitization in Subjects With Chronic Orofacial Pain: Analysis of Pain Thresholds and EEG Biomarkers - Baroni, Andrea; Severini, Giacomo; Straudi, Sofia; Buja, Sergio; Borsato, Silvia; Basaglia, Nino (Frontiers in Neuroscience, 2020)
Introduction: The presence of a temporomandibular disorder is one of the most frequent cause of orofacial pain. When pain continues beyond tissue healing time it becomes chronic, and may be caused, among other factors, by the sensitization of higher-order neurons. The aim of this study is to describe psychological characteristics of patients with chronic orofacial pain, their peripheral pain threshold and EEG recording, looking for possible signs of central sensitization. Material and methods: Twenty four subjects with chronic orofacial pain caused by temporomandibular disorder were evaluated using the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) Axis I and Axis II. Pain intensity, catastrophizing and presence of central sensitization were assessed through self-reported questionnaires. Pressure pain threshold was recorded in facial and peripheral sites; EEG activity was recorded during open and closed eyes resting state and also during the pain threshold assessment. Pain thresholds and EEG recordings were compared with a cohort of pain-free age- and sex-matched healthy subjects. Results: Patients with chronic orofacial pain showed a significant reduction in their pain threshold compared to healthy subjects in all sites assessed. Greater reduction in pain threshold was recorded in patients with more severe psychological symptoms. Decreased alpha and increased gamma activity was recorded in central and frontal regions of all subjects, although no significant differences were observed between groups. Discussion: A general reduction in pressure pain threshold was recorded in people who suffer from chronic orofacial pain. This result may be explained by sensitization of the central nervous system due to chronic pain conditions. Abnormal EEG activity was recorded during painful stimulation compared to the relaxed condition in both chronic orofacial pain subjects and healthy controls.